Oxidation of nickel-based single-crystal superalloys for industrial gas turbine applications - Sato, A; Chiu, Y; Reed, R (2011)
The oxidation resistance of three prototype single-crystal nickel-based superalloys for industrial (electricity-generating) gas turbine applications is studied. All contain greater quantities of Cr than in most existing single-crystal superalloys; two are alloyed with Si. All alloys are found to be marginal Al 2O 3-formers, with the performance being better at 1000 °C rather than 900 °C, and when Si is added. Microstructural analysis indicates that the ability to form an Al 2O 3 layer is better in the interdendritic regions; the dendritic regions are prone to internal oxidation. In all cases, an outer scale of Cr 2O 3 is formed which is in contact with either Ta 2O 5 (at 1000 °C) or NiTa 2O 6 (at 900 °C). To explain the results, the factors known to influence the rate of Al 2O 3 scale formation are considered. A model is developed to predict whether any given alloy composition will form a continuous Al 2O 3 scale. This is used to rationalize the dependence of Al 2O 3 scale formation on alloy composition in these systems. It is useful for the purposes of alloy design. © 2010 Acta Materialia Inc. Published by Elsevier Ltd. All rights reserved.